Performing Socio Drama to Increase Students' Motivation in Speaking English - Fitria Ramadhani; nazriani lubis (Indonesian Journal of ELT and Applied Linguistics, 2023)
Teaching speaking In Indonesian, many teachers have made much effort to find good methods, strategies, techniques, media and teaching materials to make the most of it. They have tried hard to maximize every way in the teaching and learning process. The socio drama method also has an influence on student learning outcomes. The purpose of the research method used is experimental. The population in this study were 250 people students of class VII SMPS PLUS Kasih Ibu Patumbak, while the sample is class VIII-A (20 students) as an experimental group that teaches storytelling techniques in narrative text and class VIII-B. (20 students) as a control group were taught without telling. This research was conducted through the following The test is a drama conversation. Researchers of several drama conversations related to English answered 2 people with drama. The results show that there is an increase in students speaking skills using storytelling techniques. After calculating the data, then the researcher found that the t-test t-test obtained that the value of observed ≥ ttable, namely 6.436 > 2.086. on significance level α = 0.5. Thus, it can be concluded that H0 is rejected and Ha is accepted. An can be interpreted that Performing socio drama significant effect on increase students' motivation in speaking english.